Cured meat intake is associated with worsening asthma symptoms. Issue 3 (20th December 2016) - Li, Zhen; Rava, Marta; Bédard, Annabelle; Dumas, Orianne; Garcia-Aymerich, Judith; Leynaert, Bénédicte; Pison, Christophe; Le Moual, Nicole; Romieu, Isabelle; Siroux, Valérie; Camargo, Carlos A; Nadif, Rachel; et al.
Abstract : Background: Cured meat intake—a recent carcinogenic factor—may increase the risk of COPD, but its association with asthma remains unknown. Though body mass index (BMI) is a likely risk factor for asthma, its role in the diet–asthma association as a mediator has never been studied. We investigated the association between cured meat intake and worsening asthma symptoms in adults, and the role of BMI as a potential mediator. Methods: Using data from the French prospective EGEA study (baseline: 2003–2007; follow-up: 2011–2013), we applied a mediation analysis in the counterfactual framework, a marginal structural model (MSM), to estimate the direct effect of baseline cured meat intake (<1, 1–3.9, ≥4 servings/week) on change in asthma symptom score (worsening or not), and the indirect effect mediated by BMI. Results: Among the 971 participants (mean age 43 years; 49% men; 42% with asthma), 20% reported worsening asthma symptoms during the mean follow-up time of 7 years. Using the MSM, we reported a positive direct effect of cured meat intake on worsening asthma symptoms (multivariable OR=1.76, 95% CI 1.01 to 3.06 for ≥4 vs <1 serving/week). We also reported an indirect effect mediated by BMI (OR=1.07; 95% CI 1.01 to 1.14), accounting for 14% of the total effect. Conclusions: Higher cured meat intake was associated with worsening asthma symptoms over time, through a direct effect and to a lesser extent an effect mediated by BMI. This research extends the effect of diet on asthma in adults.